2002
DOI: 10.1007/s00213-002-1048-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ethanol exposure in rats alters serotonergic-mediated behavioral and physiological function

Abstract: Our findings indicate that prenatal ethanol exposure alters 5-HT(1A) and 5-HT(2A) receptor function in adulthood and does so in a sex-specific manner. These findings have important implications for altered hormonal and behavioral responsiveness observed in ethanol-exposed animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Data from our lab (Hofmann et al, 2005;Weinberg, 1988Weinberg, , 1992Weinberg et al, 1996) and others Lee and Rivier, 1996) have shown that the prenatal ethanol exposure may differentially alter the HPA response pattern of females and males depending on the experimental time course, the stressor, and the hormonal endpoint measured Zhang et al, 2005). Furthermore, we have shown that DOI-induced ''wet dog shakes'' are increased in E females but not E males (Hofmann et al, 2002), and that there are sex differences in prenatal ethanol effects on anxiety and anxiolytic responses to 8-OH-DPAT (Hofmann et al, 2005). Together, these data suggest that the gonadal steroids play a role in mediating the differential effects of ethanol on females and males, and that females may be more vulnerable to the effects of in utero exposure to ethanol on 5-HT receptor-mediated responses.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Data from our lab (Hofmann et al, 2005;Weinberg, 1988Weinberg, , 1992Weinberg et al, 1996) and others Lee and Rivier, 1996) have shown that the prenatal ethanol exposure may differentially alter the HPA response pattern of females and males depending on the experimental time course, the stressor, and the hormonal endpoint measured Zhang et al, 2005). Furthermore, we have shown that DOI-induced ''wet dog shakes'' are increased in E females but not E males (Hofmann et al, 2002), and that there are sex differences in prenatal ethanol effects on anxiety and anxiolytic responses to 8-OH-DPAT (Hofmann et al, 2005). Together, these data suggest that the gonadal steroids play a role in mediating the differential effects of ethanol on females and males, and that females may be more vulnerable to the effects of in utero exposure to ethanol on 5-HT receptor-mediated responses.…”
Section: Discussionmentioning
confidence: 76%
“…Treatment with 5-HT agents normalizes many of the neuroendocrine abnormalities (Holsboer, 1999;Holsboer and Barden, 1996;Keck and Holsboer, 2001;Maes et al, 1995;Nemeroff and Owens, 2004;Rybakowski and Twardowska, 1999;Weizman et al, 1988), and the response to 5-HT has been used as a marker of clinical improvement following drug treatment (Bhagwagar et al, 2002;Raap and Van de Kar, 1999). Data from our laboratory have shown altered physiological and behavioral responses to the 5-HT 1A agonist 8-OH-DPAT (Hofmann et al, 2002) as well as an increase in anxiety-like behavior and anxiolytic responses to 8-OH-DPAT in E compared with control animals (Hofmann et al, 2005). Together with the present data showing that E animals have altered ACTH responses to 5-HT agonists and 5-HT 1A receptor mRNA expression, these findings suggest that E animals have altered 5-HT-HPA interactions, and/or an imbalance between 5-HT 1A and 5-HT 2A receptor function (Lanfumey et al, 2000;Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Twenty-four hours following the final injection, both groups were then divided into three subgroups : (1) vehicle (0.9 % saline) ; (2) 0.3 mg/kg 8-hydroxy-2-(N,N-dipropylamino)tetralin (8-OH-DPAT ; a 5-HT 1A receptor agonist ; Sigma-Aldrich, Oakville, ON, Canada) ; (3) 1 mg/kg ((1-)2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI ; a 5-HT 2A/2C receptor agonist ; Sigma-Aldrich). These doses were based on previous psychopharmacological studies and are within normal testing range (Akiyoshi et al, 1995 ;Hofmann et al, 2002 ;Mikklesen et al, 2004). Separate cohorts of animals were used for the hormonal studies (n=5 per group) and the behavioural/ thermal (n=7 per group) studies.…”
Section: Subjects and Treatmentmentioning
confidence: 99%